Subcutaneous injection of trastuzumab into the thigh versus abdominal wall in patients with HER2-positive early breast cancer: Pharmacokinetic, safety and patients' preference - Substudy of the randomised phase III GAIN-2 study. (December 2022) - Reinisch, Mattea; Untch, Michael; Mahlberg, Rolf; Reimer, Toralf; Hitschold, Thomas; Marmé, Frederik; Aydogdu, Mustafa; Schmatloch, Sabine; Lück, Hans-Joachim; Schmidt, Marcus; Ladda, Ekkehart; Sinn, Bruno Valentin; et al.
Abstract: Background: Trastuzumab given intravenously in combination with chemotherapy is standard of care for patients with early HER2-positive breast cancer (BC). Different randomised studies have shown equivalent efficacy of a subcutaneous injection into the thigh compared to the intravenous formulation. Other body regions for injection have not been investigated but might be more convenient for patients. Methods: After surgery, patients were randomised to receive either subcutaneous trastuzumab into the thigh or into the abdominal wall (AW). Patient preferences were evaluated using validated questionnaires (PINT). Primary objectives of this multicentre, non-blinded, randomised substudy of the GAIN-2 study were to investigate pharmacokinetics of the injection into the thigh versus AW and to determine patients' preferences of either administration site versus the previously received intravenous application. Results: 226 patients were randomised and 219 patients (thigh: N = 110; AW: N = 109) formed the modified intent-to-treat (mITT). Overall, 83.5% (out of N = 182 with information about patients' preference) preferred subcutaneous over previous intravenous application or had no preference. Preference was similar between both administration sites (thigh: 80.6%; AW: 86.5; p = 0.322). Pharmacokinetic analysis included 30 patients. Geometric means of Cmax and AUC0-21d were higher in thigh than in AW group (geometric mean ratio with body weight adjustment: Cmax : 1.291, 90%-CI 1.052–1.584; AUC0-21d : 1.291, 90%-CI 1.026–1.626). Safety profile was in line with previous reports of subcutaneous trastuzumab. Conclusion: Subcutaneous trastuzumab into the thigh showed an approximately 30% higher bioavailability. Injections were well tolerated and preferred over intravenous administration. The subcutaneous injection into the thigh should remain the standard of care. Highlights: The bioavailability of subcutaneous trastuzumab was 30% higher when injected the thigh vs the abdominal wall. Patients preferred subcutaneous over intravenous injection of trastuzumab. Patient preference was comparable between abdominal wall or thigh subcutaneous injection. There were no new safety signals for subcutaneous trastuzumab injection.